PAHN: A NEW HIGHLY ENERGY MOLECULE - Cubas C., R. (2010)
The new energetic material2,2,5,5,7,7-hexanitrooctahydro-1,4,3-(azanetriylmethano)-1-azacyclobuta[cd]pent alene or Poliazaheterociclo hexanitrado (PAHN) with dense and highly stressed structure has been studied theoretically describing a possible synthetic pathway_compared with traditional energetic materials. The characterization of the molecule is based on spectral analysis of the type 13C y15N RMN, UV / Vis and Infrared. The performance parameters of the detonation were estimated using the Kamlet-Jacobs equations. The calculations were carried out through the new PM6 semi-empirical method (Parametric Model 6). The optimized geometrical parameters and heats of formation were obtained by ab initio method (UHF/6-31g*) and PM6 respectively.